Odpowiedź :
Odpowiedź:
A) 5a
9x
11s
82b
18a
a
6h
a
B) -a
-2a
-2x
-11v
-b
-7d
-7x
-7w
C) -2a + 3a - 4b = a - 4b
4d + d - 3s - s = 5d - 4s
-3v - v - 3w = -4v - 3w
6y + 2x - 3y - 7x = 3y - 5x
5n - 3n - 4m - 8m = 2n - 12m
Odpowiedź:
a)
2a+3a=5a
4x+5x=9x
7s+4s=11s
4b+78b=82b
21a-3a=18a
13a-12a=a
8h-2h=6h
2a-a=a
b)
4a-5a=a
2a-4a=-2a
3x-5x=-2x
34v-45v=-11v
3b-4b=-b
-3x-4x= -7x
3w+(–7w)= -4w
c)
-2a-(-3a)+(-4b)= -5a+(-4b)
4d-(-d)+(-3s)-s= 5d+(4s)
-3v-(+v)+(-3w)= -4v+(-3w)
6y-(-2x)+(-3y)+(-7x)= 3y+(-9x)
-(-5n)-(3n)+(-4m)+(-8m)= 2n+(-12m)